THE MEDIATING ROLE OF TRANSFORMATIONAL LEADERSHIP BETWEEN EMOTIONAL INTELLIGENCE AND JOB SATISFACTION AMONG YOUNG MANAGERS - Acharya, Sopnamayee; Anand, Gunjan (International Journal of Psychosocial Rehabilitation, 2020)
Managers need leadership as a key characteristic. The pattern of behavior demonstrated consistently is considered as the leadership style [17]. In order to attain sustainable growth and development leadership proves to own an important position in whole. Leaders are the influencers, they make people see far ahead [22] and different leadership styles have their own effect on organizational effectiveness [39]. Among all the most important leadership style is transformational leadership. Burn [11] introduced the concept of transformational leadership and explained it as a process through which leaders and followers achieve higher levels of motivation and morals. Burn considered transformational leadership as a tool to bring significant change in lives of people related and further organizations too. Bernard M. Bass [8] further extended Burn work and found its measuring ways and their impact on follower’s motivation and performances. Transformational leadership style is credited for producing positive outcome in an organization further giving success to an organization [30]. When transformational and transactional leadership style were both correlated with emotional intelligence, transformational correlated more positively [5,42,23]. Emotional intelligence initially a concept given by Thorndike (1920), further Goleman gave model for the same. Emotional intelligence comprises of various things like motivation, empathy, sociability, warmth and optimism [37].